2021
DOI: 10.1371/journal.pone.0261272
|View full text |Cite
|
Sign up to set email alerts
|

Mortality predictors of hospitalized patients with COVID-19: Retrospective cohort study from Nur-Sultan, Kazakhstan

Abstract: Background First reported case of Severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) in Kazakhstan was identified in March 2020. Many specialized tertiary hospitals in Kazakhstan including National Research Cardiac Surgery Center (NRCSC) were re-organized to accept coronavirus disease 2019 (COVID-19) infected patients during summer months of 2020. Although many studies from worldwide reported their experience in treating patients with COVID-19, there are limited data available from the Centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…These findings are supported by other research studies 20,36,37 . In contrast, Yuriy Pya 31 reported no association between comorbidities and mortality in their study. However, they suggested that this may have been due to certain comorbidities going undiagnosed or incomplete data, indicating a need for further research in this area.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are supported by other research studies 20,36,37 . In contrast, Yuriy Pya 31 reported no association between comorbidities and mortality in their study. However, they suggested that this may have been due to certain comorbidities going undiagnosed or incomplete data, indicating a need for further research in this area.…”
Section: Discussionsupporting
confidence: 85%
“…In this regard, both serum iron and transferrin are found to be inversely correlated with proinflammatory cytokines such as interleukin-6; thus, low serum iron and transferrin levels are associated with a poor prognosis in SARS-CoV-2 infection cases [ 15 ]. Moreover, elevated serum ferritin levels have also been linked to an increased risk of severe COVID-19 [ 16 ], ICU admission, and mortality rate [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identified factors have included: higher age, male gender, low oxygen saturation at admission, tachypnea and various laboratory determinants such as lymphopenia, low hemoglobin levels, elevated c-reactive protein (CRP), lactate dehydrogenase (LDH) and urea, hyponatremia, hyperkalemia and abnormal coagulation parameters. 11,[18][19][20][21][22][23][24][25]…”
Section: Covid-19mentioning
confidence: 99%
“…[5][6][7][8][9] After admission to hospital, published mortality rates range widely between 2% and 60%, depending on various factors such as the type of care facility (e.g., equipped for critical care or not), hospital equipment and number and qualification of staff. [10][11][12][13][14][15] Multiple meta-analyses have estimated the in-hospital mortality to be around 17% (95% CIs ranging from 12.7% to 22.7%) 16,17 Many studies have researched predictors for in-hospital mortality. Identified factors have included: higher age, male gender, low oxygen saturation at admission, tachypnea and various laboratory determinants such as lymphopenia, low hemoglobin levels, elevated c-reactive protein (CRP), lactate dehydrogenase (LDH) and urea, hyponatremia, hyperkalemia and abnormal coagulation parameters.…”
Section: Covid-19mentioning
confidence: 99%